A novel allele, HLA‐A*33:97 was identified in a Chinese bone marrow donor. (26th October 2016) - Zhu, F.‐M.; Zhang, W.; Chen, N.‐Y.; Dong, L.‐N.; He, J.
Abstract : HLA‐A*33:97 has one base substitution at position 287 A>T in exon 2 compared to HLA‐A*33:03:01 .